CYP2C19 polymorphism frequency in Russian patients in Central Russia and Siberia with acute coronary syndrome - Mirzaev KB; Zelenskaya EM; Barbarash OL; Ganyukov VI; Apartsin KA; Saraeva NO; Nikolaev KY; Ryzhikova KA; Lifshits GI; Sychev DA (Dove Medical Press, 2017)
Karin B Mirzaev,1 Elena M Zelenskaya,2 Olga L Barbarash,3 Vladimir I Ganyukov,3 Konstantin A Apartsin,4,5 Natalya O Saraeva,4 Konstantin Y Nikolaev,6,7 Kristina A Ryzhikova,1 Galina I Lifshits,2,5,7 Dmitry A Sychev1 1Russian Medical Academy of Continuous Professional Education, Ministry of Health of the Russian Federation, Moscow, 2Federal State-Financed Research Institution “Institute of Chemical Biology and Fundamental Medicine”, Siberian Branch of the Russian Academy of Sciences, Novosibirsk, 3Federal State-Financed Research Institution “Research Institute for Complex Issues of Cardiovascular Diseases”, Siberian Branch of the Russian Academy of Sciences, Kemerovo, 4State-Financed Health Institution “Irkutsk Regional Badge of Honour Clinical Hospital”, 5Federal State-Financed Research Institution “Irkutsk Research Center”, Siberian Branch of the Russian Academy of Sciences, Irkutsk City, 6Federal State-Financed Research Institution “Research Institute of Internal and Preventive Medicine”, 7Federal State Autonomous Institution of Higher Education “Novosibirsk National Research State University”, Novosibirsk, Russia Purpose: The aim of this study is to investigate the frequency of CYP2C19*2, *3 allelic variants, associated with poor response to clopidogrel, and CYP2C19*17, associated with excessive response to clopidogrel, in patients with acute coronary syndrome (ACS) from Siberia and Moscow regions of Russia.Patients and methods: The study included 512 ACS patients who were subsequently treated with coronary arterial stenting. The subjects assigned were from the cities of Central (Novosibirsk, Kemerovo), Eastern (Irkutsk), Northern (Surgut) Siberia regions and from Moscow region. The mean age of patients enrolled was 63.9±10.9 years. Among the assigned subjects, the proportion of men accounted for 80% and women 20%.Results: According to the results obtained in the present study, from 16% up to 27.5% of patients in different regions of Russia have at least one CYP2C19 “poor metabolizer” (PM) allele variant affecting clopidogrel metabolism and, therefore, suppressing its antiplatelet activity. CYP2C19*17 allele variant was identified with the frequency of 15.4% up to 33.3%. The study revealed the presence of statistically significant differences in CYP2C19*3 allele frequency between the Russian ethnic group patients from Eastern and Central Siberia (p=0.001; odds ratio=1.05 [95% confidence interval 1.01–1.09]).Conclusion: The study revealed statistically significant differences between the allele frequencies in Eastern and Central Siberia, which can probably be caused by a considerable number of Buryats inhabiting Eastern Siberia. Keywords: P2Y12 receptor inhibitors, clopidogrel resistance, dual antiplatelet therapy